Flow cytometry analysis of CD4+IFN‐γ+ T‐cells for the diagnosis of mycobacterium tuberculosis infection. Issue 3 (8th September 2015) - Papageorgiou, Chrysovalantis V.; Anastasopoulos, Andreas; Ploussi, Maria; Leventopoulos, Michail; Karabela, Simona; Fotiadis, Kyriakos; Papavasileiou, Apostolos; Vogiatzakis, Evangelos; Ioakeimidis, Dimitrios; Gritzapis, Angelos D.; Poulakis, Nikolaos
Abstract : Background: CD4+ cells expressing Interferon‐γ (IFN‐γ), following stimulation with specific mycobacterial antigens, identified with flow cytometry (FCM‐CD4+IFN‐γ+), is a new method for the diagnosis of Mycobacterium tuberculosis (MTB) infection. The aim of this study is to investigate the performance of FCM‐CD4+IFN‐γ+ in comparison with tuberculin skin test (TST) and Quantiferon TB Gold In‐Tube (QFT‐G‐IT) in the diagnosis of latent MTB infection (LTBI), in close contacts and in patients with rheumatic diseases under treatment with anti‐TNFa and other biologic agents. Methods: TST, QFT‐G‐IT, and FCM‐CD4+IFN‐γ+ were performed in 56 immunocompetent close contacts and in 65 medically immunosuppressed patients under biologic treatment. Results: In close contacts, 63% were FCM‐CD4+IFN‐γ+ ESAT‐6(+), 70% FCM‐CD4+IFN‐γ+ PPD(+), 41% QFT‐G‐IT(+) and 57% TST(+). FCM‐CD4+IFN‐γ+ ESAT‐6 was the only test that was strongly correlated to the exposure time to infection. In the immunosuppressed group, 49% were FCM‐CD4+IFN‐γ+ ESAT‐6(+), 62% FCM‐CD4+IFN‐γ+ PPD(+), 4.6% QFT‐G‐IT(+), and 18% TST(+). Conclusion: FCM‐CD4+IFN‐γ+ assays are more sensitive than QFT‐G‐IT and TST for the diagnosis of LTBI in close contacts and in immunosuppressed patients under anti‐TNF‐a treatment. FCM‐CD4+IFN‐γ+ is not affected by the chronic use of biologic agents. © 2015 International Clinical Cytometry Society